PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL SCRAMBLE - Nur Azizah Zainudin (Institut Agama Islam Negeri Palopo, 2018)
This study aims to improve the motivation and learning outcomes of science students of class IIIb SDN 24 Temmalebba by applying a model of scramble learning on the material classification of plants based on the seeds. This research is PTK, designed through three cycles. Subjects were 39 students. Data collection techniques are observation, documentation, interviews, and tests. The research data obtained were analyzed using descriptive statistical formula to express descriptively the research result. Furthermore, to explain the results of descriptive quantitative research, used reduction analysis techniques, presentation, and conclusions. From the results of the study found that in the pre cycle, the percentage of student motivation 47.86% with the average value of students is 60, classical completeness 51.28%. After applying the scramble model, the first cycle of student motivation percentage is 62,67%, student average 70,1, 62,58% classical mastery. Furthermore, cycle II percentage of student motivation 68,10% with average value of student is 85,38, classical mastery 82,35%. Then, in the third cycle, the percentage of students' motivation reaches 78.43%, the average score of students is 88.94, 100% classical mastery. Thus, the motivation and learning outcomes of science in class III SDN Temmalebba by applying the scramble model performed on the I-III cycle showed an increase.